IMPLEMENTING A TWO-STEP DELIRIUM IDENTIFICATION PROTOCOL WITH HOSPITALIZED OLDER ADULTS: A FOCUSED ETHNOGRAPHY. (16th November 2018) - Husser, E; Shrestha, P; Gallagher, J; Boltz, M; Inouye, S; Boustani, M; Marcantonio, E; Fick, D
Abstract: The negative and often protracted impact of delirium on health, quality of life, and financial costs requires systematic, efficient screening approaches to facilitate its prompt recognition and effective treatment. As part of an NIH-funded, multi-site study that aims to validate a 2-step delirium identification protocol performed by hospital care providers (R01AG030618), this qualitative study aimed to describe the barriers and facilitators to its implementation. Focused ethnography and brief open-ended interviews, elicited the "situated" experiences of implementing the protocol from the perspectives of physicians (n=51), nurses (n=203), and nursing assistants (NAs, n= 89) in an academic medical center in Boston and a community teaching hospital in central Pennsylvania. We applied Chaudoir's Five Factor Implementation Framework to the coding and analysis of 800 + observations of protocols with older medical patients (70+) conducted over 17 months. Thematic analysis yielded the identification and categorization of major factors associated with implementation of the delirium identification process. Factors identified inform barriers as well as facilitators: 1) patient factors (affective, cognitive and physical status, coping mechanisms, social support); 2) provider factors (competing demands, skills); 3) structural factors (environmental adaptations for age-related changes, comfort, privacy); 4) organizational-level factors (staffing, morale); and 5) protocol innovation (perceived utility, efficiency). Clinicians described the protocol as efficient and having potential for integration into daily routines. As one of the first studies to test a 2-step process for delirium identification and to involve NAs, our findings have role implications and describe the need for a multi-faceted, systemic approach to implementation.